Vocal Features of Song and Speech: Insights from Schoenberg's Pierrot Lunaire - Merrill, Julia; Larrouy-Maestri, Pauline (Frontiers in Psychology, 2017)
Similarities and differences between speech and song are often examined. However, the perceptual definition of these two types of vocalization is challenging. Indeed, the prototypical characteristics of speech or song support top-down processes, which influence listeners' perception of acoustic information. In order to examine vocal features associated with speaking and singing, we propose an innovative approach designed to facilitate bottom-up mechanisms in perceiving vocalizations by using material situated between speech and song: Speechsong. 25 participants were asked to evaluate 20 performances of a speechsong composition by Arnold Schoenberg, “Pierrot lunaire” op. 21 from 1912, evaluating 20 features of vocal-articulatory expression. Raters provided reliable judgments concerning the vocal features used by the performers and did not show strong appeal or specific expectations in reference to Schoenberg's piece. By examining the relationship between the vocal features and the impression of song or speech, the results confirm the importance of pitch (height, contour, range), but also point to the relevance of register, timbre, tension and faucal distance. Besides highlighting vocal features associated with speech and song, this study supports the relevance of the present approach of focusing on a theoretical middle category in order to better understand vocal expression in song and speech.